Beyond blackface: African Americans and the creation of American popular culture, 1890 - 1930 - Brundage, William Fitzhugh (H. Eugene and Lillian Youngs Lehman series, 2011)
Black misrepresentation in nineteenth-century sheet music illustration / Stephanie Dunson -- Creating an image in Black : the power of abolition pictures / John Stauffer -- The real thing / David Krasner -- Black creativity and Black stereotype : rethinking twentieth-century popular music in America / Susan Curtis -- Crossing boundaries : Black musicians who defied musical genres / Thomas Riis -- Our newcomers to the city : the great migration and the making of modern mass culture / Davarian L. Baldwin -- Buying and selling with God : African American religion, race records, and the emerging culture of mass consumption in the South / John M. Giggie -- The secret life of Oscar Micheaux : race films, contested histories, and modern American culture / Robert Jackson -- Hear me talking to you : the blues and the romance of rebellion / Grace Elizabeth Hale -- At the feet of Dessalines : performing Hait's revolution during the new Negro renaissance / Clare Corbould -- The Black eagle of Harlem / Shane White ... [et al.] -- More than a prizefight : Joe Louis, Max Schmeling, and the transnational politics of boxing / Lewis A. Erenberg